Neutrophil Lymphocyte Ratio is an Indicator of Coronary Artery Disease - Bhuiyan, Mohammad Monzurul Alam; Sultana, Sanjida; Yesmin, Shaila; Pramanik, Amit Kumar; Hasan, Amanat; Jabed, Syed Md.; Paul, Debatosh; Sultana, Tuhin (Archives of Clinical and Biomedical Research, 2022)
Neutrophil Lymphocyte Ratio (NLR) is the sign of balance between neutrophil lymphocyte levels in the body and an indicator of systemic inflammation. NLR is a new predictor for cardiovascular risk and mortality. This study aims to assess the Neutrophil Lymphocyte Ratio (NLR) as a useful indicator for coronary artery disease (CAD). This case control study was conducted in the Department of Clinical pathology in collaboration with Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from March 2014 to February 2015. Total 134 patients were enrolled in this study who were waiting for further percutaneous coronary intervention (PCI) in the Department of Cardiology, BSMMU; 84 cases were considered as Group I (Patients with CAD) and 50 controls were Group II (Patients without CAD). A 2 ml of blood was collected in EDTA tube from the patients prior to PCI for complete blood count (CBC) were measured by haematology autoanalyzer, rechecked manually and NLR was calculated in the Department of Clinical Pathology, BSMMU. NLR was higher in Patients with CAD group compared to Patients without CAD (2.76 (±0.74) vs 1.56 (±0.15), p<0.001). NLR may be a useful marker to predict the presence of CAD.